Indian Ethnomedicinal Phytochemicals as Promising Inhibitors of RNA-Binding Domain of SARS-CoV-2 Nucleocapsid Phosphoprotein: An In Silico Study - Muthumanickam, Sankar; Kamaladevi, Arumugam; Boomi, Pandi; Gowrishankar, Shanmugaraj; Pandian, Shunmugiah Karutha (Frontiers in Molecular Biosciences, 2021)
SARS-CoV-2, an etiological agent of COVID-19 has been the reason for unexpected global pandemic causing severe mortality and imposes devastative effects in public health. Despite of extensive research work put forward by scientist around globe, so far, no suitable drug or vaccine (with safe, affordable and efficacious) has been identified to treat SARS-CoV-2. As an alternative way of improvising COVID-19 treatment strategy, i.e. strengthening of host immune system, a great deal of attention has been given to phyto-compounds from medicinal herbs worldwide. In a similar fashion, the present study deliberately focuses on the phytochemicals of three Indian herbal medicinal plants viz., Mentha arvensis, Coriandrum sativum and Ocimum sanctum for their efficacy to target well recognized viral receptor protein through molecular docking and dynamics analyses. Nucleocapsid phosphoprotein (N) of SARS-CoV-2 being a pivotal player in replication, transcription and viral genome assembly, it has been recognized as one of the most attractive viral receptor protein targets for controlling the viral multiplication in host. Out of 127 phytochemicals screened, nine (Linarin, Eudesmol, Cadinene, Geranyl acetate, Alpha-thujene, Germacrene A, Kaempferol-3-O-Glucuronide, Kaempferide and Baicalin) were found to be phenomenal in terms of exhibiting high binding affinity towards the catalytic pocket of target N protein. Further, the ADMET prediction analysis unveiled the non-tumorigenic, non-carcinogenic, non-toxic, non-mutagenic and non-reproductive nature of the identified bioactive molecules. Furthermore, the data of molecular dynamics simulation validated the conformational and dynamic stability of the docked complexes. Concomitantly, the data of the present study validated the anti-COVID efficacy of the bioactives from selected medicinal plants of Indian origin.